Kisruh Regulasi Tenaga Kerja Asing Sebagai Kegagalan Komunikasi Publik Pemerintah - Firdausi, Indrianti Azhar; Fuqoha, Fuqoha (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
The development of information technology should be maximized by the government in establishing communication and information about policies taken by the government. Thus, good communication will be held in order to achieve the goals of the State without the social upheaval that arises in the community due to policies set by the government. One of the failures of government public communication is the government's failure to explain and socialize the Presidential Regulation Number 20 of 2018 concerning the Use of Foreign Workers who get responses to the pros and cons of all parties, both from the general public and from government opposition. The communication failure gave birth to multi-interpretation from various circles of society and government. Every government regulation or legal policy has functions and objectives in order to achieve the goals of the State. Conception The rule of law guarantees legal certainty, legal benefits and legal justice. The regulation on the use of foreign workers is one form of legal certainty in order to protect opportunities and employment opportunities for citizens of their own country. However, communication failures built by the government resulted in multi-interpretation of policies that were considered to provide convenience for foreign workers and complicate Indonesian employment opportunities.